2016
DOI: 10.3906/zoo-1506-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal (cadmium, lead, and chromium) contamination infarmed fish: a potential risk for consumers’ health

Abstract: To assess heavy metal loads in cultured fish, four farmed carp fish species were sampled from a fish farming cluster at the Head Qadirabad area. Samples were randomly collected from fish farms and a local fish market and analyzed for three nonessential heavy metals, cadmium (Cd), chromium (Cr), and lead (Pb), at Fish Quality Control Labs Manawan, Lahore, Pakistan. All three tested metals were found in all samples of selected fish species. The highest accumulation among heavy metals in farmed carps was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 5 publications
2
3
1
Order By: Relevance
“…When compared to cultivated Nile Tilapia and lake fish, Nile Tilapia can absorb contaminants with long biological half-lives, such as, Cd, and Pb, throughout a long lifespan. These findings agree with Chatta et al (2016), who reported that the farmed Cirrhinus mrigala and Labeo rohita accumulated less Cd and Pb than the lake ones. Lake fish also had higher levels of nonessential heavy metals due to a longer lifetime and exposure, but they also had reduced levels of essential metals because they were not fed a commercial diet (Simukoko et al, 2022).…”
Section: Assay Of Heavy Meals In Water and Fish Tissuessupporting
confidence: 93%
“…When compared to cultivated Nile Tilapia and lake fish, Nile Tilapia can absorb contaminants with long biological half-lives, such as, Cd, and Pb, throughout a long lifespan. These findings agree with Chatta et al (2016), who reported that the farmed Cirrhinus mrigala and Labeo rohita accumulated less Cd and Pb than the lake ones. Lake fish also had higher levels of nonessential heavy metals due to a longer lifetime and exposure, but they also had reduced levels of essential metals because they were not fed a commercial diet (Simukoko et al, 2022).…”
Section: Assay Of Heavy Meals In Water and Fish Tissuessupporting
confidence: 93%
“…The values for the Pd, Cr were lower as compared to the values evaluated by the Chatha et al (2016) who reported higher values for these metals and indicate the increasing concentration level of metals in the farmed fishes in Head Qadirabad area along the Chenab River and declare them not safe for human consumption due to the presence of Pb, beyond acceptable limits. Similarly the values of Pd in the trimmu and Balloki headworks were higher than that of allowable ranges thus, the fish in that water bodies were not fit for human consumption.…”
Section: Resultscontrasting
confidence: 59%
“…Permissible limit of Cadmium as recommended by the FAO (2011) as 0.05 as in present study within range. This implies Cd as not taken above as limit as by Ashraf and Nazeer (2010) and Chatta et al (2016). Accumulations of Pb in study found below than maximum permissible limit as (FAO, 1984) reported similar concentration of lead in Ctenopharyngodon idella as in the present study.…”
Section: Discussionsupporting
confidence: 72%